Insomniacs after school. 5 - Ojiro, Makoto, 1982- (Viz signature., 2024)
"Following the disappointment of the canceled meteor shower viewing party, Nakami and Isaki switch their focus to the photography contest and head out on an astronomy club trip with Isaki's sister, Haya. Isaki and Nakami come back from a night of snapping photos to find Haya leaving. Now they're all alone together in the countryside. How will this change their relationship?"--Back cover.